2014
DOI: 10.15249/6-2-29
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of ethics, environmental, social and governance criteria

Abstract: Responsible investing (RI) is a growing phenomenon in the international investment arena. This article investigates the level of knowledge of members of South African pension/provident funds with regard to RI and the importance with which they view various ethical, environmental, social and governance (ESG) criteria. Respondents (n = 281) indicated a relatively low level of understanding of the concept of RI. Significant differences were noted in the perceptions of respondents about the relative importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
3
3
0
Order By: Relevance
“…The demographic characteristics of the social investors are an important factor for understanding their attitudes and behavior [33]. In this study, age was a control variable, but not a significant one; this finding supports the previous literature [27,90]. In addition, the education level of investors had an insignificant effect on the investment decision, which contradicts the previous literature [26,27], which indicated that an educated investor would be more concerned about ethical, environmental, social, or governance issues.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The demographic characteristics of the social investors are an important factor for understanding their attitudes and behavior [33]. In this study, age was a control variable, but not a significant one; this finding supports the previous literature [27,90]. In addition, the education level of investors had an insignificant effect on the investment decision, which contradicts the previous literature [26,27], which indicated that an educated investor would be more concerned about ethical, environmental, social, or governance issues.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, age was a control variable, but not a significant one; this finding supports the previous literature [27,90]. In addition, the education level of investors had an insignificant effect on the investment decision, which contradicts the previous literature [26,27], which indicated that an educated investor would be more concerned about ethical, environmental, social, or governance issues. A possible explanation for these findings might be the presence of a comparatively well-educated investor pole in the stock markets of Bangladesh.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The concepts RI and CSR are closely linked. Whereas CSR focuses on wealth creation from the perspective of firms, RI considers wealth creation from the viewpoint of investors (Viviers, Krüger & Venter 2012).…”
Section: Clarification Of Relevant Termsmentioning
confidence: 99%
“…The term socially responsible investment (SRI) is essentially underpinned by ethical requirements to shape the market, while the RI concept integrates both ESG and financial aspects into mainstream investment decision-making (Van Der Ahee & Schulschenk 2013). Since the launch of the United Nations Principles for Responsible Investment (UN PRI), more researchers and practitioners have been using the term 'responsible investing' rather than 'socially responsible investing' (Viviers et al 2012).…”
Section: Clarification Of Relevant Termsmentioning
confidence: 99%